Exercício agudo realizado a baixo ou acima do limiar anaeróbio induz diferentes comportamentos de ansiedade em ratos wistar - Lima, Carleuza Francisca de (2007)
Few studies have investigated the acute/chronic effects of physical exercises on behaviors related to anxiety in animal models and the results are quite contradictory. Those conflicts seem to result from the methodological diversity among the studies, for example, the configuration of the physical exercise program. Materials and methods. Male Wistar rats were randomly divided in 4 groups: Control, 0, 5 or 50% of the body weight. The effect of the intensity of the swimming exercise on the behavioral measurements in the tests of elevated plus-maze and open field were investigated. Results. The variance analysis revealed significant differences on the concentration of blood lactate among the groups (p < 0.01). The analyses revealed that the 50% group showed smaller stay time and entrance in the open arms of the maze compared to the Control one, and to the groups of 0% and 5% of body weight. The animals submitted to a smaller level of physical stress revealed a higher disposition - up to 54% - to stay in the open arms when compared with the Control group. Conclusions. The results suggest that the acute effects of the physical exercise result in complex and transitory changes of behavior and central neurochemistry in rats. Those changes seem to follow a charge-response ratio that depends on the intensity of the exercise.